2004
DOI: 10.1104/pp.104.050369
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Seedling Growth Response and Recovery to Ethylene. A Kinetic Analysis

Abstract: Responses to the plant hormone ethylene are mediated by a family of five receptors in Arabidopsis that act in the absence of ethylene as negative regulators of response pathways. In this study, we examined the rapid kinetics of growth inhibition by ethylene and growth recovery after ethylene withdrawal in hypocotyls of etiolated seedlings of wild-type and ethylene receptor-deficient Arabidopsis lines. This analysis revealed that there are two phases to growth inhibition by ethylene in wild type: a rapid phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
228
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(243 citation statements)
references
References 38 publications
12
228
1
2
Order By: Relevance
“…The production of new receptors in response to ethylene has been proposed as a mechanism to reset the ethylene sensitivity of the plant (3,40). Thus, the increase in levels of receptor/CTR1 complexes with ethylene concentrations up to 1 l/liter would serve to desensitize the plant to ethylene, thereby facilitating the adaptation response to ethylene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of new receptors in response to ethylene has been proposed as a mechanism to reset the ethylene sensitivity of the plant (3,40). Thus, the increase in levels of receptor/CTR1 complexes with ethylene concentrations up to 1 l/liter would serve to desensitize the plant to ethylene, thereby facilitating the adaptation response to ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…7. Ethylene perception and signal transduction induce the production of new ethylene receptors, ERS1, ETR2, and ERS2 all being primary response genes whose transcription is rapidly induced in response to ethylene (40,41). The increase in overall ethylene receptor levels at the membrane results in a concurrent increase in membrane-associated CTR1 levels due to the physical association of CTR1 with the receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Other Arabidopsis ethylene receptors had Ser kinase activity (Moussatche and Klee, 2004). The functions of the ETR1 kinase domain and its kinase activity are relatively weak in induction of ethylene response and seedling growth recovery after ethylene removal, and the signal output by the ETR N terminus is dependent on subfamily I members Binder et al, 2004;Qu and Schaller, 2004;Xie et al, 2006). The ETR1 receptor function can be regulated by RTE1 or the copper transporter RAN1 Resnick et al, 2006).…”
mentioning
confidence: 99%
“…The receptors have homology to bacterial two-component receptors that transduce signals via the autophosphorylation of a His residue in the kinase domain, followed by the transfer of phosphate to a conserved Asp residue in the receiver domain of a response regulator protein (9). Although some of the receptors are capable of His kinase activity (10,11) and ethylene may inhibit this activity in ETR1 (12), kinase activity is not needed for signaling (13)(14)(15). The N terminus of these receptors contains the novel ligand-binding domain (16 -18), and a number of studies have now identified amino acid residues in the three ␣-helices of ETR1 that are important for ethylene binding and signal transduction (16, 19 -21).…”
mentioning
confidence: 99%